Lumbar intervertebral disc calcification with massive herniation: a case report - Junxin Chen; Kangmao Huang; Song Dai; Yuanhang Chen; Wenbin Xu; Xiangqian Fang (Journal of International Medical Research)
An 18-year-old female patient presented with a 1-month history of low back pain, which had worsened and was accompanied by radiating pain in the right lower limb for half a month. She was admitted to our hospital with computed tomography and magnetic resonance imaging findings suggesting calcification of the L3/4 disc and a large intraspinal mass at the L2–4 level. The patient’s symptoms did not improve with conservative treatment, and her muscle strength rapidly declined. Therefore, a right-sided L3 laminotomy was performed for decompression. Intraoperatively, a cystic intraspinal mass with calcification was observed, and upon incision, a toothpaste-like substance flowed out. Pathological examination revealed fibrous tissue with glassy deposits and calcifications. Postoperatively, the patient’s symptoms resolved completely, with no recurrence observed at the 2-month follow-up and complete resorption of the calcification at the L3/4 disc. Idiopathic intervertebral disc calcification with massive herniation poses a risk of permanent nerve function loss, and timely decompression is recommended to ensure a good prognosis.